Active axial spondyloarthritis: potential role of certolizumab pegol - Ranatunga S; Miller AV (Dove Medical Press, 2014)
Sriya Ranatunga, Anne V Miller Department of Internal Medicine, Southern Illinois University School of Medicine, Springfield, IL, USA Abstract: The axial spondyloarthropathies are a group of chronic inflammatory diseases that predominantly affect the axial joints. This group includes ankylosing spondylitis and nonradiographic axial spondyloarthropathy. While the pathogenesis of axial spondyloarthropathies is not clear, immunologically active tissues primarily include the entheses, ie, the areas where ligaments, tendons, and joint capsules attach to bone and to the annulus fibrosis at the vertebrae. One of the major mediators of the immune response in this group of diseases is tumor necrosis factor-alpha (TNFα). Blockade of TNFα results in reduced vascularity and inflammatory cell infiltration in the synovial tissues of affected joints. Certolizumab pegol (CZP) is an Fc-free, PEGylated anti-TNFα monoclonal antibody. CZP has unique properties that differ from other available TNFα inhibitors by virtue of its lack of an Fc region, which minimizes potential Fc-mediated effects, and its PEGylation, which improves drug pharmacokinetics and bioavailability. It has been shown in clinical trials that CZP improves patient outcomes and reduces inflammation in the sacroiliac joints and spine in both ankylosing spondylitis and nonradiographic axial spondyloarthropathies. These data support CZP as a treatment option for axial spondyloarthropathies. Keywords: axial spondyloarthropathy, certolizumab pegol, anti-tumor necrosis factor-alpha, therapy